Performance Management in Improving Competitiveness Educational Institution at MAN 2 Blitar - Azizah M.R, Naila; Qomar, Mujamil; Naim, Ngainun (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This research is motivated by the intense competition in the education sector, where many institutions experience a decline in performance due to low productivity of human resources. Well-implemented performance management has the potential to enhance the effectiveness and efficiency of the institution, as well as strengthen its competitiveness. The focus of this research includes the reasons why the principal pays special attention to performance management, strategies for building the performance spirit of teachers and staff, and its implications for the competitiveness of the educational institution at MAN 2 Blitar. This research uses a qualitative phenomenological approach with data collection techniques through observation, interviews, and documentation. The research results indicate that the principal plays an important role in setting performance standards, managing transparent performance evaluations, encouraging collaboration, and improving the quality of learning and operational efficiency. The strategies implemented include open communication, recognition of staff achievements, and support for professional development. The implications of good performance management are improved learning quality, better decision-making, and enhanced school reputation. With the implementation of this strategy, MAN 2 Blitar successfully enhanced its competitiveness in the education sector.